PENGARUH CUSTOMER TRUST DAN PERCEIVED USEFULNESS TERHADAP KEPUTUSAN MENGGUNAKAN APLIKASI BANK DIGITAL DENGAN DIMEDIASI BEHAVIORAL INTENTION - Mariana Roe Kothan; Muhamad Yunanto (Bisnis-Net, 2026)
This research aims to analyze the influence of customer trust and perceived usefulness on the usage decision of SeaBank digital banking application, with behavioral intention as a mediating variable. The background of this research is the rapid development of digital banking services in Indonesia, especially the SeaBank application, but the adoption rate is not always linear with the growth of internet users. The research method uses a quantitative approach with a survey of 150 SeaBank customers in the Jabodetabek area. Data were analyzed using Structural Equation Modeling (SEM-PLS). The results showed that customer trust has a positive and significant effect on behavioral intention, while perceived usefulness does not have a significant effect on behavioral intention. Customer trust and perceived usefulness have a positive and significant effect on the usage decision of the SeaBank application. Behavioral intention was proven to mediate the influence of customer trust on the usage decision, but it does not mediate the influence of perceived usefulness on the usage decision. This research provides theoretical implications in the development of technology adoption models and practical implications for SeaBank management in increasing user loyalty.